Cellular Profiles of Prodynorphin and Preproenkephalin mRNA-Expressing Neurons in the Anterior Olfactory Tubercle of Mice - Maegawa, Ayako; Murata, Koshi; Kuroda, Kazuki; Fujieda, Shigeharu; Fukazawa, Yugo (Frontiers in Neural Circuits, 2022)
The olfactory tubercle (OT) is a striatal region that receives olfactory inputs. mRNAs of prodynorphin (Pdyn) and preproenkephalin (Penk), precursors of dynorphins and enkephalins, respectively, are strongly expressed in the striatum. Both produce opioid peptides with various physiological effects such as pain relief and euphoria. Recent studies have revealed that OT has anatomical and cytoarchitectonic domains that play different roles in odor-induced motivated behavior. Neuronal subtypes of the OT can be distinguished by their expression of the dopamine receptors D1 (Drd1) and D2 (Drd2). Here, we addressed whether and which type of opioid peptide precursors the D1- and D2-expressing neurons in the OT express. We used multiple fluorescence in situ hybridization for mRNAs of the opioid precursors and dopamine receptors to characterize mouse OT neurons. Pdyn was mainly expressed by Drd1-expressing cells in the dense cell layer (DCL) of the OT, whereas Penk was expressed primarily by Drd2-expressing cells in the DCL. We also confirmed the presence of a larger population of Pdyn-Penk-Drd1 co-expressing cells in the DCL of the anteromedial OT compared with the anterolateral OT. These observations will help understand whether and how dynorphins and enkephalins in the OT are involved in diverse odor-induced motivated behaviors.